2017
DOI: 10.15416/ijpst.v4i1.8982
|View full text |Cite
|
Sign up to set email alerts
|

Aktivitas Antibakteri Ekstrak Etanol Dari Lima Tanaman Terhadap Bakteri Staphylococcus Epidermidis Dengan Metode Mikrodilusi M7 – A6CLSI

Abstract: Abstrak Antibacterial Activity Of Five Plant Ethanol Extract Against Staphylococcus Epidermidis Bacteria With Microdilution M7 -A6CLSI Method AbstractThe antibacterial activity of Leucaena leucocephala, Camellia sinensis, Psidium guajava L, Anredera cordifolia (Ten.) Steenis and Solanum nigrum L. leafs ethanol extract against Staphylococcus epidermidis using microdillution method has been studied. Using microdillution method with tetracycline, chloramfenicol and amoxicillin as antibiotic reference. Leucaena le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 10 publications
0
5
0
9
Order By: Relevance
“…Chahyono dan Suryana mengemukakan bahwa biji lamtoro mengandung semyawa aktif seperti flavonoid, tanin, saponin, alkaloid dan mimosin [7], [8] . Namun, sampai saat ini belum ada informasi mengenai pemanfaatan biji lamtoro sebagai insektisida alami.…”
Section: Pendahuluanunclassified
“…Chahyono dan Suryana mengemukakan bahwa biji lamtoro mengandung semyawa aktif seperti flavonoid, tanin, saponin, alkaloid dan mimosin [7], [8] . Namun, sampai saat ini belum ada informasi mengenai pemanfaatan biji lamtoro sebagai insektisida alami.…”
Section: Pendahuluanunclassified
“…Pada penelitian terdahulu diketahui bahwa ekstrak etanol daun petai cina terbukti mempunyai aktivitas antibakteri terhadap Staphylococcus epidermidis [5] dan Staphylococcus aureus [6]. Penelitian antibakteri pada fraksi daun petai cina belum banyak dilakukan, oleh karena itu dinilai penting untuk melakukan penelitian lebih lanjut terhadap fraksi senyawa daun petai cina yang memiliki aktivitas antibakteri paling baik.…”
Section: Pendahuluanunclassified
“…The antibacterial activity of LLE ointment is caused by the ethanol extract of L. leucocephala leaf that contains secondary metabolites. Previous research has found that LLE comprises flavonoids, tannins, and saponins that have antibacterial properties (Suryana et al, 2017). Also, it possesses phytol (terpene compounds) and squalene (triterpene compounds), which are efficacious as antibacterial (Zayed and Samling, 2016;Suryana et al, 2017).…”
Section: Samplesmentioning
confidence: 99%
“…Another study with Gas Chromatography (GC) has identified the presence of terpenes, along with squalene as a secondary metabolite in LLE (Awe, 2013;Mohammed et al, 2015;Negi et al, 2016). Flavonoids, tannins, terpenes, and triterpene are known as phytochemical substances that have antibacterial properties (Aderibigbe, 2011;Mohammed et al, 2015;Negi et al, 2016;Zayed and Samling, 2016;Suryana, 2017). In other words, previous studies have confirmed that L. leucocephala leaf extract (LLE) has antibacterial properties.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation